The impact of minimal residual disease prior to unmanipulated haploidentical hematopoietic stem cell transplantation in patients with acute myeloid leukemia in complete remission. Issue 5 (4th May 2017) - Zhao, Xiao-Su; Qin, Ya-Zhen; Liu, Yan-Rong; Chang, Ying-Jun; Xu, Lan-Ping; Zhang, Xiao-Hui; Huang, Xiao-Jun
Abstract: The minimal residual disease (MRD) before and after a haploidentical hematopoietic stem cell transplantation (HSCT) of 86 patients with acute myeloid leukemia (AML) in complete remission (CR) was measured using flow cytometry (FCM) and Wilms tumor 1 (WT1). In all, 18 patients met the criteria of pre-MRD + before HSCT. The FCM + ( p  = .028) and the combinative criteria for positive MRD (MRDco+) ( p  = .022) post-transplantation were significantly correlated to relapse in univariate analysis. A multivariate analysis showed that only MRDco + post-transplantation was an independent risk factor of leukemia relapse ( p  = .022, HR = 4.653, 95% CI: 1.249–17.334). A significant difference in the cumulative incidence of relapse between patients with or without post-transplant MRDco + was observed ( p  < .001). However, the results suggested that the MRD status before transplantation might not affect leukemia relapse of patients with AML in CR after haploidentical HSCT. These types of patients might not need to receive further intensive chemotherapy or active intervention concerning HSCT.